THE EFFECTIVENESS OF TRAINING IN THE CREATION OF EDUCATIONAL GAMES IN AN INTERACTIVE ENVIRONMENT IN COMPUTER SCIENCE - Sagimbayeva А.Е.; Nietbaeva Н.А. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
The purpose of the article is to show the effectiveness of teaching the creation of educational games using an interactive environment in additional education in computer science. The purpose of teaching the creation of educational games in the conditions of additional education in computer science is to form students’ knowledge, skills and abilities necessary for an interesting and effective learning experience using games and other interactive technologies. To teach the creation of educational games using an interactive learning environment, expert methods were used in the selection of educational material. With the help of questionnaires, the method of group and expert evaluation for choosing the content of computer game programming training was considered, the concepts of descriptors for teaching the creation of educational games using an interactive learning environment were defined. Each expert was offered the concepts necessary to create computer science training games according to the level of their use. The use of an interactive environment in the conditions of additional education in computer science in general can help explain the practical significance of studying the methodology of teaching students to create learning games, improve results, stimulate the creation of learning games, as well as the development of skills and knowledge of students.